1998
DOI: 10.1039/a807321j
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of iron reduction potential by deprotonation at a remote site

Abstract: Remote site deprotonation of a coordinated imidazole ligand switches the reduction potential of coordinated iron over a narrow pH range from +0.920 to 20.460 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
42
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 14 publications
(19 reference statements)
9
42
0
Order By: Relevance
“…This wave falls in the same potential window as the Ni III/II couple for other tetraanionic ligands. [1,[22][23][24][25] Therefore the difference of about 600 mV between the first anodic waves is consistent with the previously reported values for the deprotonation of a coordinated imidazole group [9,11] ( % 300 mV drop per proton). The corollary to this downshift of the first oxidation wave is the concomitant disappearance of the reduction wave observed at À1.88 V. Both of these changes observed for the electrochemical behaviour of the nickel(II) complex upon deprotonation demonstrate the higher field strength generated by the deprotonated imidazole groups.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…This wave falls in the same potential window as the Ni III/II couple for other tetraanionic ligands. [1,[22][23][24][25] Therefore the difference of about 600 mV between the first anodic waves is consistent with the previously reported values for the deprotonation of a coordinated imidazole group [9,11] ( % 300 mV drop per proton). The corollary to this downshift of the first oxidation wave is the concomitant disappearance of the reduction wave observed at À1.88 V. Both of these changes observed for the electrochemical behaviour of the nickel(II) complex upon deprotonation demonstrate the higher field strength generated by the deprotonated imidazole groups.…”
supporting
confidence: 89%
“…In the case of non-heme complexes, Williams and co-workers were the first to show a drastic drop in the redox potential of a non-porphyrinic iron complex upon deprotonation of four ligated imidazole moieties. [11] Analysis of the electrochemical data revealed a drop of around 300 mV shift per proton. However, attempts to elucidate the processes involved have been realised by using a coordinatively saturated iron complex to prevent any structural change in the coordination sphere of the metal ion.…”
Section: Introductionmentioning
confidence: 99%
“…In an extensive study of redox reactions of complexes of ruthenium and osmium containing benzimidazole subunits, Haga et al 19,20 measured the effect of deprotonation of a coordinated benzimidazole ligand on the M(III)/M(II) reduction potential to be a shift of ~300 mV/proton in the negative direction. Williams et al 21 have recently reported the structure and electrochemistry of an iron(II) complex of a 2,6-diimidazolyl pyridine, [Fe(H 2 (6)) 2 ] 2+ (see Figure 1). The potential for the Fe(III)/Fe(II)couple of [Fe(H 2 (6)) 2 ] 2+ is found at +0.920 mV vs NHE in acetonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…Six-coordinatedsodium(I)environments are present in the most of the comparativelyf ew sodium(I)c omplexes, such as in 1,7-bis(2,2¢ -dihydroxybiphen-3-yl)-4,10-dimethyl-1,4,7,10-tetraazacyclododecane)sodium acetonitrile solvate [1], tetrakis(acetonitrile) bis(tetrahydrofuran)sodium bis(2,6-bis-benzimidazol-2-yl)pyridine)iron [2] and bis(2-(4¢ -thiazolyl)benzimidazole-N , N ¢ ) bis(octadeuterofuran)sodium [3]. Inthe course of studies of phenanthroline complexes, we have synthesized the title mononuclear …”
Section: Discussionmentioning
confidence: 99%